Klik, Swipe, Akhlak: Building a Generation of Character Through Islamic Religious Education in the Digital Era - Dita Durotun Nufus (Seutia Hukamaa Cendekia, 2026)
The rapid advancement of digital technology has revolutionized educational practices, including Islamic Religious Education, while simultaneously presenting ethical and moral challenges for students in the digital age. This study aims to examine the role of Islamic education in fostering students’ character and digital ethics in the digital era. Employing a library research approach, the study analyzed scholarly articles, books, and national and international journal publications on Islamic education, digital literacy, and character education published between 2020 and 2025. The collected data underwent thematic categorization and critical interpretation. The findings reveal that digital technology offers significant opportunities to enhance accessibility, interactivity, and collaboration in Islamic education. However, the digital era also contributes to moral challenges, including misinformation, cyberbullying, declining digital ethics, and weak character development among students. Therefore, Islamic Religious Education should not merely focus on technological adaptation but must also strengthen students’ moral awareness by integrating Islamic ethical values into digital activities. This article contributes by proposing the concept of “digital akhlak” as a framework for incorporating Islamic values like tabayyun, amanah, iffah, tawadhu’, and ukhuwah into students’ digital behavior. The study emphasizes the strategic role of Islamic education in preparing morally responsible digital citizens capable of navigating the challenges of the twenty-first century.